Preliminary study for catalytic gasification of water hyacinth for syngas production - April Ling Kwang, Chee; Bridgid Lai Fui, Chin; Shaharin Anwar, Sulaiman; Chai, Yee Ho; Agus, Saptoro; Hadiza Aminu, Umar; Lam, Man Kee; Yiin, Chung Loong (2023)
Water hyacinth being one of the top invasive aquatic plants has brought upon various challenges towards the humanity and the environment. The magnitude of the menace of uncontrollable growth and spread of water hyacinth has sparked the interest of researchers in identifying its potential as a biomass feedstock for biofuel production. Biomass gasification is deemed as a promising green technology which is capable of converting biomass into value-added commodity. Conversion of such large quantity of biomass into biofuel via gasification does not only help to promote sustainable resource utilization but also facilitates the reduction of global carbon impacts and engender socioeconomic development. The addition of catalysts to the gasification process could enhance the formation of gaseous products where the gas composition may be altered. This study aims to present the preliminary study on the gasification performance of water hyacinth biomass in a lab scale fixed-bed downdraft gasifier (67 mm diameter and 750 mm height), with the use of air as the gasifying agent in a batch feeding of 50 grams for each run. The results showed that temperature has a substantial effect on the gasification of water hyacinth whereby hydrogen produced was raised from 2.92 vol.% to 11.19 vol.%. Further gasification tests are expected for the optimization of the main process parameters such as biomass particle size and catalyst loading.